Model Pedukung Keputusan Dengan Metode Analitycal Hierarchy Process: Studi Kasus Proses Bongkar Muatan Barang Kapal - Ari Muzakir (APTIKOM SUMSEL, 2021)
As a center for leaning ships, the Port is a center that plays an important role as a facility that can connect one island to another in trading activities. In this study emphasizes the final goal of (1) determining the factors used as criteria for determining the right and optimal loading decisions, (2) calculating the priority weights of the decision criteria, (3) determining priority weights, (4) obtaining a design that best in priority ship unloading. In this study we use hierarchical based analysis methods or commonly called Analytical hierarchy process (AHP). This method performs pairwise comparisons between criteria and sub criteria by producing a criteria value matrix and produces consistent information each factor from the sub-criteria assessed where the CR <0.1. The results of the scores for each 3 respondents are where the arrival time of the ship scores a total of 17.46 with the highest score, the type of load total score of 11.89, the type of ship the total score is 6.61 and the total loading score of 3.05.